A study on demographic and obstetric profile, its relation with present antenatal practices and prevalence of anaemia in pregnant women attending tertiary care hospital - Lodha, Nitin A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Antenatal care is the care of a woman during pregnancy. The primary aim of antenatal care is to achieve at the end of pregnancy a healthy mother and a healthy baby. To improve maternal health, barriers which limit access to quality maternal health services must be identified and addressed at all levels of health system. Objectives were to determine demographic and obstetric factors affecting utilization of ANC service and prevalence of anaemia among pregnant women. Methods: This is cross-sectional descriptive study carried out in tertiary care hospital, using structured questionnaire, interviews were conducted with married pregnant women age between 18-45 years, who visited ANC clinic. Total 170 pregnant women visited hospital during a period was included in study. Data was analysed using MS excel and Epi info. Chi –square test was applied. Results: Maximum number of study subjects (42.9%) from age 23-27 years. 66.5% were Hindu, 56.5% study subjects from joint family. 14.7% were illiterate. 45.3% were primigravida, 54.7% were multigravida. 71.1% study subjects were from third trimester of pregnancy. 94.7% were taken at least one dose of Tetanus Toxoids. Iron folic acid tablets were taken by 87.6%. Prevalence of anaemia was 55.8%. Conclusions: Majority of pregnant women came for antenatal check-up, but regularity was not seen in most of cases. The presence study has brought out no significant socio-cultural barrier like women’s literacy, socio economic class and parity of women affecting the utilization of services.